The birth, operations and demise of Zimbabwe Inter-Africa News Agency (Ziana) - Mandava, Peter (Midlands State University, 2015)
In the first place, the paper locates the creation of alternative news agencies in the realm of Third World nations' struggles for self-determination in all aspects of their lives. The arguments of the paper are that ZIANA was founded on noble ideas but was undermined by a number of factors that included: weak capital base from point of inception and along the way, ownership structure not preferred by larger part of media industry, lack of corporate identity, lack of a profit-motive drive in the core-business of gathering and selling news and generally poor managerial and administrative skills. The paper concludes that these problems if not addressed, most preferably in a holistic manner, will constitute an insidious worm that render the second experiment another still birth.